BLENDED LEARNING AS A LEARNING INNOVATION IN THE ERA OF THE INDUSTRIAL REVOLUTION 4.0 AT UNIVERSITY (International Conference on Social and Islamic Studies, 2022)
In the era of the industrial revolution 4.0, educators must be able to innovate, especially in the teaching and learning process so that learning can be more optimal and interesting. Technological developments require educators to have skills, be able to innovate, think critically, communicate, and master technology. The purpose of this study was to find out how tertiary institutions utilize blended learning as an innovation in learning in the 4.0 industrial revolution era in tertiary institutions. This type of research is library research which discusses blended learning as learning innovation in the era of the industrial revolution 4.0 in tertiary institutions. The technique used in this study to collect data is using documentation obtained through books and journals that are relevant to the topics discussed in this paper. This study uses data analysis techniques, namely content analysis. Learning innovations using blended learning provide opportunities for students with various characteristics to be able to learn independently, sustainably, throughout their lives so that learning will be effective, efficient, interesting and fun. The design is based on Behaviorism and cognitive constructivist learning theory with the specifications of its components including: 1) learning outcomes, 2) material organization maps, 3) reference lists, 4) teaching materials/materials, 5) synchronous and asynchronous learning activities, asynchronous learning designs, 6) synchronous learning design, 7) synchronous learning flow.